1989
DOI: 10.1302/0301-620x.71b1.2914976
|View full text |Cite
|
Sign up to set email alerts
|

The blood supply of the calcaneal tendon

Abstract: The microvascular anatomy of the calcaneal tendon was investigated in cadaver tendons by injection of barium sulphate and indian ink and a quantitative study of intratendinous blood supply was made, using a computer-assisted image analysis system. There was a reduction in both the number and the mean relative area of vessels in the mid-section of the tendon. This area of reduced vascularity may be of significance in the pathogenesis of rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
159
3
15

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(183 citation statements)
references
References 0 publications
6
159
3
15
Order By: Relevance
“…Lim et al [20] described a 3% rerupture rate, Haji et al [13] a 2.6% rate, and Amlang et al [3] a 3.2% rate. In contrast to these findings, we found no reruptures in our percutaneous repair group, and for the open group, our finding is similar to that reported in the literature [8,10,12]. Another of the most described complications for the percutaneous approach is sural nerve injury [13,20,21,23].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lim et al [20] described a 3% rerupture rate, Haji et al [13] a 2.6% rate, and Amlang et al [3] a 3.2% rate. In contrast to these findings, we found no reruptures in our percutaneous repair group, and for the open group, our finding is similar to that reported in the literature [8,10,12]. Another of the most described complications for the percutaneous approach is sural nerve injury [13,20,21,23].…”
Section: Discussionsupporting
confidence: 89%
“…Two patients had wound dehiscence, and one had subsequent surgery. The cause of wound complication associated with open surgery is presumably owing to the poorly vascularized skin surrounding the Achilles tendon [8] and length of the incision compared to percutaneous surgery, exposing soft tissue and causing inevitably greater damage to it. Rerupture is a described complication of the percutaneous technique, with different rates reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The Achilles tendon receives its blood supply from three regions; the myotendinous junctions, osteotendinous junctions and the paratenon (Schatzker and Brånemark, 1969, Carr and Norris, 1989, O'Brien, 1997. It has been reported that the midportion of the Achilles tendon has a lower vascular supply compared with the rest of the tendon (Lagergren andLindholm, 1959, Carr andNorris, 1989).…”
Section: Circulationmentioning
confidence: 99%
“…It has been reported that the midportion of the Achilles tendon has a lower vascular supply compared with the rest of the tendon (Lagergren andLindholm, 1959, Carr andNorris, 1989). More recent studies have reported contradictory results.…”
Section: Circulationmentioning
confidence: 99%
“…Normally, avascular fibrocartilage is found on the tendon surface that is directed towards the pulley [36]. This concept has been supported by a number of morphological and experimental studies [3][4][5]13 for the development of overuse injuries and degenerative changes [6,12,18,19,22,38]. The reasons for the development of avascular zones in gliding regions of tendons are largely unknown.…”
Section: Introductionmentioning
confidence: 98%